(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
This study aimed to analyze the impact of CO2 emissions on the economic growth of India. The preliminary analysis of the data showed that CO2 emissions are on the rise in India. Further, the analysis showed that carbon emissions are lower from the gaseous fuel consumption than electricity and heat production, and manufacturing industries, and construction. Similarly, the carbon emissions from liquid fuel consumption are lower than those from electricity and heat production but higher than those from manufacturing and construction. The analysis of the data proves that there is a connection between these variables. Results of correlation analysis and regression analysis showed that carbon emissions have a negative and significant impact on India’s economic growth. Based on these results, we conclude that reducing carbon emissions is critical for the country’s well-being. As a result, the government should devise strategies to reduce carbon emissions that are environmentally benign. Environmental protection is a long process requiring ongoing planning, government regulations, and public and industrial participation.